Is the Economic Mechanism of Quantity-Quality Tradeoff Sustainable? - Pieńkowski, Dariusz (Problemy Ekorozwoju, 2019)
The contemporary economic debate on population ageing points out low fertility and the economic threats to pensioners, although the global population increased more than two and a half times in 1950-2015. The socio-economic problems are conflicting with the ecological debate and the attempts to stabilise population growth within a sustainable scale. This paper researches a tradeoff mechanism between quality and quantity of children offered by G. Becker from a global evolutionary perspective postulated in the conception of sustainable development. The balance between quality and quantity results in the lower fertility typical of many developed countries. However, it does not correspond with the lower ecological deficit in these countries according to the determinants postulated in IPAT. The conclusion here is that there is no effective economic mechanism to balance affluence and population change. This research shows that the present demographic problems are rooted in the socio-economic institutions and there is no problem with lower fertility or ageing population from the global perspective.